Type 1 invariant natural killer T cells in chronic inflammation and tissue fibrosis - Kumar, Vipin; Hertz, Marc; Agro, Albert; Byrne, Adam J. (Frontiers in Immunology, 2023)
Chronic tissue inflammation often results in fibrosis characterized by the accumulation of extracellular matrix components remodeling normal tissue architecture and function. Recent studies have suggested common immune mechanisms despite the complexity of the interactions between tissue-specific fibroblasts, macrophages, and distinct immune cell populations that mediate fibrosis in various tissues.Natural killer T (NKT) cells recognizing lipid antigens bound to CD1d molecules have been shown to play an important role in chronic inflammation and fibrosis. Here we review recent data in both experimental models and in humans that suggest a key role of type 1 invariant NKT (iNKT) cell activation in the progression of inflammatory cascades leading to recruitment of neutrophils and activation of the inflammasome, macrophages, fibroblasts, and, ultimately, fibrosis. Emerging evidence suggests that iNKT-associated mechanisms contribute to type 1, type 2 and type 3 immune pathways mediating tissue fibrosis, including idiopathic pulmonary fibrosis (IPF). Thus, targeting a pathway upstream of these immune mechanisms, such as the inhibition of iNKT activation, may be important in modulating various fibrotic conditions.